Analisis Kemampuan Pemecahan Masalah Matematis Siswa pada Penyelesaian Soal Cerita Pecahan di Sekolah Dasar - Nugraha, Efrina Salma; Zakia, Neneng; Anggelia, Syarah Fitri; Burhanudin, Bubun; Alpian, Yayan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The ability to solve mathematical problems is the lowest ability in learning Math story problems in grade 5 at one of the public elementary schools in Kotabaru Subdistrict, Karawang Regency. This is the background for the researcher to conduct the study. This study aims to find out the extent of students' mathematical problem-solving abilities in solving addition and subtraction of fractions story problems, as well as the faktors that affect the success or failure of students in this case. This research is a case study with a qualitative method conducted by collecting data through tests and interviews with 5 student subjects. The results show that the average mathematical problem-solving ability of students is 57.6, which can be categorized as sufficient. Faktors affecting students' abilities include internal faktors such as intelligence, interest, talent, attitude, and communication skills, as well as external faktors such as the role of parents and teachers in guiding and teaching students.